2015
DOI: 10.3892/ol.2015.3194
|View full text |Cite
|
Sign up to set email alerts
|

Solamargine triggers hepatoma cell death through apoptosis

Abstract: Abstract. Solamargine (SM), a steroidal alkaloid glycoside extracted from the traditional Chinese herb Solanum incanum, has been evidenced to inhibit the growth and induce apoptosis in a number of human cancer cell lines. In the present study, the anticancer effect of SM and underlying molecular mechanism of SM-induced apoptosis were investigated on the human hepatocellular carcinoma cells, SMMC7721 and HepG2. The proliferation effects of SM on the SMMC7721 and HepG2 cell lines were evaluated using MTT and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Steroidal glycoalkaloids are naturally occurring nitrogen containing secondary metabolites found in plants of the Solanaceae family. Solamargine, a steroidal alkaloid glycoside extracted from the traditional Chinese herb Solanum incanum , has been reported to have various pharmacological functions including anti-cancer activities [22, 50, 51]. Although there were important discoveries revealed by other studies indicated multiple signaling pathways and molecular genes or proteins that involved in the anti-tumor responses of solamargine, the in-depth molecular mechanisms by which this agent in inhibition of tumor growth still remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Steroidal glycoalkaloids are naturally occurring nitrogen containing secondary metabolites found in plants of the Solanaceae family. Solamargine, a steroidal alkaloid glycoside extracted from the traditional Chinese herb Solanum incanum , has been reported to have various pharmacological functions including anti-cancer activities [22, 50, 51]. Although there were important discoveries revealed by other studies indicated multiple signaling pathways and molecular genes or proteins that involved in the anti-tumor responses of solamargine, the in-depth molecular mechanisms by which this agent in inhibition of tumor growth still remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the doses of SM increased, the suppression effect was enhanced. In the wound-healing assay, it was hypothesized that the width of the gap would decrease in a time-dependent manner, whereas after 24 h of treatment with 10 and 20 µM concentrations of SM, the width of the gap was increased compared with the size of the gap following 12 h. It was considered that this phenomenon was associated with the SM function in triggering HepG2 cells death by apoptosis (21). Use of a Matrigel-coated Transwell assay is a classical method to detect cell invasion, whereby the invasive HepG2 cells would digest the gel and penetrate the upper chamber to the lower wells.…”
Section: Discussionmentioning
confidence: 99%
“…Certain previous studies have reported that they Chinese herbs served important roles in regulating tumor cell behavior, including proliferation, apoptosis and metastasis (25)(26)(27). SM, extracted from Solanum incanum, is a traditional Chinese herb that was demonstrated to possess an effective function in inducing apoptosis of HepG2 and SMMC7721 cells in our previous study (21). In the present study, as conclusive results were not previously observed when investigating metastasis in SMMC7721 cells, the effects of SM on the migration and invasion on HepG2 cells were evaluated, and the concentration and treated durations were used as referenced in our previous study (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic tumor cells possess several distinctive characteristics; they undergo epithelial-mesenchymal transition (EMT) and become invasive, become resistant to apoptosis and anoikis, and acquire the ability to disseminate and colonize secondary sites. SM inhibits the migration and invasion viability of HepG2 cells by blocking EMT [33] [34] [38].…”
Section: Metastasismentioning
confidence: 99%